If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 115 = -5(1 + 6x) 115 = (1 * -5 + 6x * -5) 115 = (-5 + -30x) Solving 115 = -5 + -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. 115 + 30x = -5 + -30x + 30x Combine like terms: -30x + 30x = 0 115 + 30x = -5 + 0 115 + 30x = -5 Add '-115' to each side of the equation. 115 + -115 + 30x = -5 + -115 Combine like terms: 115 + -115 = 0 0 + 30x = -5 + -115 30x = -5 + -115 Combine like terms: -5 + -115 = -120 30x = -120 Divide each side by '30'. x = -4 Simplifying x = -4
| -3(4x-4)=60 | | 25x^2+30x+9=4x^2-4x+1 | | (64u^5)^(2/3) | | -85=4(3x-3)-1 | | Y=1/2×6-6 | | Y+5y+7=43 | | -6-4x-6=12 | | 2x+60=2 | | (5x-3)2=(2x-1)2 | | 16u^(10/3) | | 6c-3=-18+x | | 1/2×6-6 | | -10=n+2+5n | | 1+lgx=lg(x+1) | | 8-3i/7-2i | | 3=v+7+3v | | 4x-1+6=-1 | | -1=1/2x-6 | | -1+5k=9 | | y^2=4/9x | | 5x-3=ln(12) | | u-644/10=19 | | 2=x+1+1 | | 6=1-c | | 6(5-r)+4(-1-r)=6 | | 20(x)+6(y)=634 | | 9(z+6)=72 | | 2a+3b=-13 | | -2(-6x-2)+6(x-1)=-2 | | 2(c-14)=34 | | 8a+24=4a-12 | | -2(n+3)-5(n+3)=7 |